STIMULASI BENIH KETIMUN (Cucumis sativus L.) GUNAMENINGKATKAN PRODUKSIBUAH - Rd Prasodjo Soedomo (Research Center for Biology-Indonesian Institute of Sciences, 2006)
The cucumber (Cucumis sativus L.) sex epression commonly monoceous and diaceous, however are dominated by male flowers.The percentage of female flower are only under 5% of total flowers per plant. Due to the environmental effects, the female flowers are usually fall down, thus fruitset decreased. The objective of this research is to increase the potential of female flowers to set fruits, thus impacted on fruit yield increase of cucumber by application of methyl blue and soaking seeds. The study was conducted at Kalijati Sub-District (+ 96 m asl), Subang District, West Java Province between May to June 2006 (dry season), in latosol reddish soil. The experiment was designed under a randomized block in factorial model, with twelve combination treatmeants and three replications.The the treatmeants were: A. concentration methyl blue: (Al) control (0 %), (A2) 0,03 %, (A3) 0,06 % and (A4) 0,09 %. B. the length of soaking: (Bl) 12 hours, (B2) 24 hours and (B3) 36 hours. The results shows that the stimulation of cucumber seeds in 0,03%, 0,06% and 0,09% compared to control, increasing the female flowers ability to set fruits up to 62,65%,45,61% and 13,79% respectively; and had impacted to increase yield per plant up to 40,69%, 34,48% and 14,09%. The stimulation of cucumber seeds by 0.03, 0.06 and 0.09% of methyl blue were able to increase the potential of female flowers to set fruits 62,65,45,61 and 13,79 % respectively. Meanwhile it has impacted in increasing fruits yield per plant up to 40,69%, 34,48% and 14,09%. The effect of 0,06% and 0,09% of methyl blue concentration, showed on the decrease of survival plants (28,42% and 37,73 %),seed germination (3 and 5 days) and the initiation of flowering time (1 and 2 days). The longer the seeds are soaked in methyl blue solution, there were tendencies in decreasing the potential of female flowers to set fruits thus fruits yields; also the percentage of plants to develop, longer germination period and decreasing the possibility of female flowers to set fruit.